2004
DOI: 10.1124/jpet.103.060319
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Multiple P2Y Receptors in Trabecular Meshwork Cells

Abstract: The purpose of this study was to determine whether functional purinergic P2 receptors are present in trabecular meshwork cells. The human trabecular cell line HTM-3 and cultured bovine trabecular cells were used to assess the effects of P2 agonists on intracellular Ca 2ϩ levels, extracellular signal-regulated kinase (ERK1/2) activation, and P2Y receptor expression. ATP, UTP, ADP, and 2-methyl-thio-adenosine triphosphate (2-MeS-ATP) each produced a concentration-dependent increase in intracellular Ca 2ϩ in bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Using the same antibodies, it was possible to identify these receptors in rat ocular structures such as the corneal epithelium (P2Y 6 ) and the retinal pigmented epithelium (P2Y 11 ) and to confirm the existence of P2Y 1 and P2Y 2 in sections containing the TM (Pintor et al, 2004). Other studies have also reported the presence of P2Y 1 and P2Y 2 receptors in bovine TM cells (Cui et al, 2001) and P2Y 1 , P2Y 4 , and P2Y 11 in a human TM cell line (Crosson et al, 2004). Ap n As are known to activate several different purinergic receptors: Ap 3 A and Ap 4 A both activate P2Y 1 receptors with different selectivity, whereas Ap 5 A is, in general, less effective at this receptor (Schachter et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same antibodies, it was possible to identify these receptors in rat ocular structures such as the corneal epithelium (P2Y 6 ) and the retinal pigmented epithelium (P2Y 11 ) and to confirm the existence of P2Y 1 and P2Y 2 in sections containing the TM (Pintor et al, 2004). Other studies have also reported the presence of P2Y 1 and P2Y 2 receptors in bovine TM cells (Cui et al, 2001) and P2Y 1 , P2Y 4 , and P2Y 11 in a human TM cell line (Crosson et al, 2004). Ap n As are known to activate several different purinergic receptors: Ap 3 A and Ap 4 A both activate P2Y 1 receptors with different selectivity, whereas Ap 5 A is, in general, less effective at this receptor (Schachter et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3) (Crosson et al, 2004;Soto et al, 2004), bradykinin (Llobet et al, 1999), and carbachol (Shade et al, 1996). Interestingly, drugs that induce large and sustained Ca 2ϩ mobilizations either decrease outflow facility (bradykinin, carbachol, and endothelin-1) (Wiederholt et al, 1995;Llobet et al, 1999) or do not modify it (Up 4 U and ATP; this study and D. Soto and X. Gasull, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA, protein, and functional evidence have been found for purinergic receptors P2Y 1 , P2Y 2 , P2Y 4 , and P2Y 11 in the bovine trabecular meshwork (Figure 1) [101, 102] and in the human HTM-3 cell line [103]. Depending on the purinergic receptor activated, an increase or decrease in aqueous humor outflow is found.…”
Section: Ocular Sensory Innervation and Purinergic Receptors P2 Inmentioning
confidence: 99%
“…Effect on the trabecular meshwork. Trabecular meshwork presents many P2Y receptors, mainly P2Y 1 , P2Y 2 , and P2Y 4 in bovine TM cells (Soto et al, 2005) and P2Y 11 in a cellular line of human trabecular meshwork (Crosson et al, 2004). Diadenosine polyphosphates do not activate all these receptors in the same way.…”
Section: Presence In the Aqueous Humourmentioning
confidence: 99%